The Roles and Sustainability of Local Institutions of Mangrove Management in Pahawang Island - Indra Gumay Febryano; Didik Suharjito; Dudung Darusman; Cecep Kusmana; Aceng Hidayat (Institut Pertanian Bogor (IPB University), 2014)
Local institutions along with community participation are crucial things in a sustainable development. Collective actions performed by a community in managing natural resources have led to success, but local institutions are also facing challenges to institutional sustainability. This research aimed to elucidate and explain the roles and sustainability of local institutions of mangrove management. This research is a qualitative research, using a case study method Research results showed that the majority of community support and admit that mangroves in their region as Mangrove Preservation Area under controlled by management of local organization with agreed rules. Nevertheless, the inability of local organizations to enforce such rules when facing investors and politics in the local level has caused these organizations to elude their support and institutional status. It is for this reason that local institutions need to be strengthened through collaboration among local institutions, local, national and international NGOs, universities, research institutions, and many others. Such collaboration can improve bargaining position of local institutions, so that finally can promote regency government policies which favoring more to local institutions. Mangrove management in a sustainable way by local institutions will help regency government in rural development.